Impact of the US presidential race on the German economy: Insights from professional forecasters - Alexander Glas; Lora Pavlova; Julius Schölkopf (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2024)
This policy brief analyses German professional forecasters' views on the upcoming US presidential election in November 2024 and its impact on the German economy. Depending on its outcome, the election can have a differential effect on Germany's foreign trade policy due to intensive trade ties between the USA and Germany. Furthermore, the USA has been one of the key supporters of Ukraine, providing billions in financial and military aid since Russia's invasion in 2022. Our analysis is based on recent data from the ZEW's Financial Market Survey (Finanzmarkttest, FMT), a long-standing survey of financial market experts and professional forecasters in Germany. The FMT is well-known for producing the ZEW Indicator of Economic Sentiment, one of the most important indicators for the German economy. For our analysis, we first asked respondents to assess the likelihood of a Trump victory, conditional on several events that may affect the election outcome. Next, we elicited scenario-based forecasts for German GDP growth and inflation over the upcoming president's tenure, depending on whether Trump or Harris wins the election. To better understand the differences in the conditional macroeconomic expectations, we asked the panellists which candidate they thought is more likely to achieve certain economic or political outcomes. Lastly, we included an open-ended question on possible measures the German government could take now to protect the German economy from potential adverse effects of the next US president's policies.
Keywords: 330